Implications of biosensors and nanobiosensors for the eco-friendly detection of public health and agro-based insecticides: A comprehensive review - Sagnika Samal; Rashmi Priya Mohanty; Priti Sundar Mohanty; Mrunmay Kumar Giri; Sanghamitra Pati; Biswadeep Das (Heliyon, 2023)
Biosensors, in particular nanobiosensors, have brought a paradigm shift in the detection approaches involved in healthcare, agricultural, and industrial sectors. In accordance with the global expansion in the world population, there has been an increase in the application of specific insecticides for maintaining public health and enhancing agriculture, such as organophosphates, organochlorines, pyrethroids, and carbamates. This has led to the contamination of ground water, besides increasing the chances of biomagnification as most of these insecticides are non-biodegradable. Hence, conventional and more advanced approaches are being devised for the routine monitoring of such insecticides in the environment. This review walks through the implications of biosensors and nanobiosensors, which could offer a wide range of benefits for the detection of the insecticides, quantifying their toxicity status, and versatility in application. Unique eco-friendly nanobiosensors such as microcantilevers, carbon nanotubes, 3D printing organic materials and nylon nano-compounds are some advanced tools that are being employed for the detection of specific insecticides under different conditions. Furthermore, in order to implement a smart agriculture system, nanobiosensors could be integrated into mobile apps and GPS systems for controlling farming in remote areas, which would greatly assist the farmer remotely for crop improvement and maintenance. This review discusses about such tools along with more advanced and eco-friendly approaches that are on the verge of development and could offer a promising alternative for analyte detection in different domains.